HUBUNGAN PANJANG DAN BERAT, FAKTOR KONDISI , FEKUNDITAS, DAN PERKEMBANGAN TELUR IKAN TENGADAK (Barbonymus schwanenfeldii) DARI SAROLANGUN, JAMBI DAN ANJONGAN, KALIMANTAN BARAT, INDONESIA - Irin Iriana Kusmini; Jojo Subagja; Fera Permata Putri (BERITA BIOLOGI, 2018)
Tinfoil barb (Barbonymus schwanenfeldii) is one of the potential local fish to be cultivated as a food or pet fish. The data and information of the growth pattern of species are essential for fish farming success. The observation on the length and weight relationship is an usefull indicator to determine the pattern of growth fish observed. This study aims to determine the growth patterns of tinfoil barb fish based on length and weight relationship, condition factor and fish fecundity of tinfoil barb from Sarolangun, Jambi and Anjongan, West Kalimantan. The 30 samples were taken randomly from each group. Data were analyzed using analysis regression Microsoft Excel. The result showed that the regression coefficient of length and weight relationship was 2.811 for Sarolangun and 2.686 for Anjongan. The regression value indicates that the the growth of tinfoil barb was allometric negative, with an average factor condition ranged from 0.99 to 1.002. Length and weight relationship had determinant value (R2) ranged from 0.79 to 0.96, with the fecundity ranged from 20168 to 232.040 eggs from 9–45.5g of gonad weight.